The impact of sludge return liquors on South African wastewater treatment plants - Olivier Nsengiyumva; Yuva Coothen; David Ikumi; Kirshen Naidoo (Water SA, 2021)
There have been three considerable shifts, in the past 20 years, in the conventional design and modelling of wastewater treatment plants (WWTPs): (i) single unit process to plant-wide modelling, (ii) consideration of WWTPs as water and resource recovery facilities (WRRFs), and (iii) the need to simplify WWTP models to allow their intake by new stakeholders (i.e. plant operators, designers and decision-makers) who use these models for evaluation of WWTP optimisation strategies. The latter shift has prompted the debate about model complexity versus the required modelling purpose among modellers. In addition to the aforementioned shifts, there has been limited research on the impact of sludge recycling dewatering liquor on the overall plant performance, especially in the context of South African WWTPs. A simplified full-scale steady-state WWTP simulation tool was developed, based on principles of sound mass-balance stoichiometry and rate-limiting kinetics. This tool enables the user to analyse the impact of recycling the DWL on the plant performance through different scenarios. The strategic scenarios evaluated included the implementation of two side-stream treatment processes (STPs), namely BABE and struvite precipitation. The evaluation of various strategies was done using the benchmark simulation model (BSM) task group plant performance indices (i.e. effluent quality and operational cost indices, EQI and OCI, respectively) incorporated into the simplified steady-state full-scale models. The integration of STP in the WWTP layout results in better EQI and OCI. The composition of the DWL affects the choice of the STP to be used, i.e., for DWL from an AD treating WAS that is not P-rich the recommended side-stream treatment operation would be the BABE process rather than struvite precipitation.